Miti o učenju drugega/tujega jezika - Nagode, Gabrijela (Vestnik za tuje jezike, 2016)
There exist several myths about second/foreign language learning. Many of them might have been "fossilised" by second/foreign language users. The article highlights a selection of four myths on second/foreign language learning. Myth 1 is that the sooner one starts to learn a second/foreign language, the better they will learn it. Myth 2 is that transfer from L1 is the major source of errors in a second/foreign language. Myth 3 is that the teacher should correct errors as soon as they appear to prevent the student from remembering them. Myth 4 is that the best way to learn new vocabulary is through reading. Finally we conclude that myths on second/foreign language acquisition are complex, which is true for the myths presented in this paper, too. The least plausible seems to be myth 3 about the urgency of immediate correction of errors. Myths 1, 2 and 4 seem to be true, although with certain limitations.
Keywords: tuji jeziki; drugi jezik; didaktika jezika; neresnice